Concave curvature facets benefit oxygen electroreduction catalysis on octahedral shaped PtNi nanocatalysts. Issue 3 (20th December 2018) - Kühl, S.; Gocyla, M.; Heyen, H.; Selve, S.; Heggen, M.; Dunin-Borkowski, R. E.; Strasser, P.
Abstract : PtNi alloy nano-octahedra after thermal reductive annealing: imperfect PtNi octahedra with concave Pt curvature catalytically outperform well-alloyed cuboctahedral nanoparticles with {111} and {100} nanofacets in electrochemical ORR. Abstract : Studies that demonstrated enhanced electrocatalytic oxygen reduction activities of octahedral PtNi nanocatalysts have routinely motivated and explained their data by the structure-sensitivity of PtNi alloy surfaces in general, more specifically by the favourable performance of the annealed Pt3 Ni(111) single crystal surface with a monoatomic Pt skin, in particular. In this contribution, we challenge this view and show that imperfect Ni-enriched {111} nanofacets with concave Pt curvature catalytically outperform flat, well-alloyed, locally ordered {111} and {100} nanofacets in cuboctahedral nanoparticles. To achieve this, we investigate the geometric, compositional, and morphological structure on the ensemble and on the individual particle level of PtNi alloy nano-octahedra. In particular, we track the correlations of these parameters after thermal annealing and link them to their catalytic activity. The level of local compositional and structural disorder appears to be a reliable descriptor and predictor for ORR activity – at least within a family of catalysts. After annealing up to 300 °C, concave Pt {111} facets, with partially flat Ni facets, remained most prevalent, resulting in nanoparticles with pronounced elemental anisotropy. At higher annealing temperature, concave Pt morphologies gave way to cuboctahedra with healed flat {111} and {100} alloy facets. The imperfect concave nano-octahedral catalysts with enhanced local disorder invariably outperformed more ordered particles, yet lagged behind in morphological stability. Faceted PtNi nano-cuboctahedra emerging at 400 °C ultimately offered the most reasonable balance between moderately high activity and good morphological stability. This is why we propose these cuboctahedral shaped Pt alloy nanoparticles as promising PEM cathode fuel cell catalyst of choice. While the present results do not invalidate the exceptional oxygen reduction activity of perfect Pt3 Ni(111) "skin" single crystal surfaces, they shed new light on the decade old puzzle about structure–activity relationships of PtNi octahedral nanocrystals.